2017
DOI: 10.5812/msnj.81173
|View full text |Cite
|
Sign up to set email alerts
|

Coping Behaviors in Parents of Children with Thalassemia major

Abstract: Background and Aims: Parents of children with thalassemia major, as the main caregivers, encounter numerous challenges in coping with various and complicated problems due to the disease of their children. Although the coping strategies of the parents regarding the illness of their children are of high importance, a few studies have been performed on this subject. Therefore, the present study aimed to determine the coping behaviors of parents of children with thalassemia major. Methods: This cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Prayers was perceived by caregivers as a strategy to express emotions, feelings and support for expressing their hopes and wishes for their child. The same is true in the study by Kermansaravi et al, 17 which found that parents of the children with thalassemia used coping behaviors by turning to God since this can strengthen the feeling of mental stability.…”
Section: Spiritualitysupporting
confidence: 59%
See 2 more Smart Citations
“…Prayers was perceived by caregivers as a strategy to express emotions, feelings and support for expressing their hopes and wishes for their child. The same is true in the study by Kermansaravi et al, 17 which found that parents of the children with thalassemia used coping behaviors by turning to God since this can strengthen the feeling of mental stability.…”
Section: Spiritualitysupporting
confidence: 59%
“…As such, the findings from the studies were presented as a narrative summary under five core themes: illness belief, health literacy, social interaction and communication, social and family support, and spirituality. Full-text articles assessed for eligibility (n= 57) Wacharasin et al 2015 4 Anum & Dasti 2016 14 Efe et al 2012 15 Nabors et al 2013 16 Kermansaravi et al 2018 17 Chusri et al 2019 18 Maheen et al 2015 19 Zaheer et al 2015 20 Habibzadeh et al 2012 21 Gold…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It concluded that the most prevelant coping behavior used by mother and father include "I read more about the medical problems that worry me and turn to god" and "I show that I am strong". 7 The current study concluded that the most expressed coping behavior used by caregivers was "Talking with the doctor about my concerns, about my child(ren) with the medical condition" and "believing that my child is getting the best medical care possible".…”
Section: Discussionmentioning
confidence: 80%
“…Parents and family members of those children who are suffering with beta thalassemia major face acute depression and anxiety (Kermansaravi et al 2018 ). Such feelings originated from the perception that beta thalassemia major is a life sacking disease may ultimately result in a general pessimism about life in the suffering children and their families as well (Mohamadian et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%